Hubungan Pemberian Asi Eksklusif Terhadap Perkembangan Bayi Usia 6-12 Bulan Berdasarkan Koesioner Pra-Skrining Perkembangan (KPSP) - Hasriati, Wa ode; Musrif, Fitriyanti; wahid, Wa Ode Putri Agustina (Madu : Jurnal Kesehatan, 2024)
One of the efforts to improve infant growth and development is to provide exclusive breastfeeding. Breast milk contains the best nutrients because it contains all nutrients in the ideal amount and composition. National data from the Indonesian Ministry of Health in 2019, 16% of young children in Indonesia experience developmental disabilities, including delays in gross motor, fine motor, and speech, and are not yet independent. The purpose of this study was to determine the relationship of exclusive breastfeeding to the development of infants aged 6-12 months in the Kadolomoko Health Centre working area. The type of research used was Cross Sectional with a retrospective approach, the samples taken were infants aged 6-12 months with incidental sampling technique. The number of samples in this study amounted to 102 samples. Statistical analysis using computer programme. Univariate analysis test to determine the characteristics of samples and respondents. Then the bivariate test was carried out, namely the Chi Square test to determine whether there was a relationship between variables. The Chi Square test results showed a p-value of 0.144 which is greater than the 5% alpha value (0.05), indicating that there is no relationship between exclusive breastfeeding and child development aged 6-12 months.